جوهر علم الدلالة في القرآن (دراسة تحليلية دلالية في قراءة الآيات القرآنية) - Ahmadi, Ahmadi (LISANIA: Journal of Arabic Education and Literature, 2018)
The semantic study pioneered by Izutsu is an analytical study of basic language terms with the aim of ending achieving conceptual understanding - people who use the language - not only as a medium of communication, speaking and thinking, but more important is the formulation and interpretation of the surrounding environment. This semantic research aims to present its purpose about the semantic concept of expressions in the Qur'an. The application of the semantics in the Qur'an study based on Izutsu is an analytical study of key terms in the language of the Qur'an to achieve a conceptual understanding of Qu’ran's view about the world. In other words, it attempts to detect human perceptions of the universe and life are reflected in the Qur’an, the conceptual system where it originates, and which contextual meanings give new words and meanings, key words that represent messages in understanding of a particular topic or the semantic field belongs to another group of words. There are for example semantic fields (Mufhomat systems revolving around coherent themes, Ukrawy fields) and keyword expressions which are considered as keys to understanding the meaning in this semantic field. And there is also what he calls the core word (al-Kalimah Al-Sameimah), the conceptual center of the important lexicon semantic sector, including a number of specific keywords.